The concept of character in narratology - Thomka, Beáta (Anafora, 2014)
Varying interpretations of fictional worlds or the diversity and frequent confusion of categories need not hinder our perception of the protagonist as a bundle of values, quality, organization, sounds, characteristics and signs. A character is a moral construct, the storage of representation; it can be revealed through his or her actions and must thus be understood and interpreted accordingly. It is a complex whole of imaginary constructs, even in those poetics of novels which – based on a disbelief in human integrity – separate the character from his/her mental psychic and social determinants and show him/her as a representative of a particular life situation. The lack of logic of narrative understanding in some twentieth-century narrative works begs for the recognition of metaphoric principles, which at the same time determines the strategy of the interpretation as well. The source of the theoretical orientation of this paper is based on the work and spiritual heritage of two thinkers. Bakhtin’s view of the natural world as processual (questions concerning poetics, aesthetics and ethics) and Ricœur’s conception of narrative poetics and theory of uniformity is equally emphasized on the one hand as a construction of fictional characters and, on the other, as a possibility for the development of self-understanding. Apart from Ricœur’s study Narrative Identity, Bakhtin’s essay "Author and Hero" (emerged around 1920) served as an inspiration for a brief interpretation of two significant short stories, Flaubert’s "A Simple Heart" and Mann’s "Death in Venice".